2023
DOI: 10.3390/su15054483
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations on Dual-Fuel Engine Fueled with Tertiary Renewable Fuel Combinations of Biodiesel and Producer—Hydrogen Gas Using Response Surface Methodology

Abstract: The effects of producer gas (PG), hydrogen (H2), and neem oil methyl ester-blended fuel (NeOME B20) flow rate optimization on dual fuel (DF) engine performance were examined in the current work. PG and H2 were used as primary fuels, while NeOME B20 was used as a secondary pilot fuel in the DF engine. The DF engine’s performance and pollution levels were optimized using response surface methodology (RSM) and the results were compared with experimental values. The full factorial design (FFD) has been used to min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Halewadimath et al [24] varied the H 2 content in the inducted PG to improve the performance of DF engines using neem oil biodiesel blends. They noticed that in the presence of H 2 the ignition delay period was reduced with a decrease in combustion duration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Halewadimath et al [24] varied the H 2 content in the inducted PG to improve the performance of DF engines using neem oil biodiesel blends. They noticed that in the presence of H 2 the ignition delay period was reduced with a decrease in combustion duration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Alina et al [22] used the RSM to optimize the extraction yield of biologically active compounds from crushed Merlot grapes using ultrasound treatment before maceration. Sushrut S. et al [23] optimized fuel flow rates in a DF engine using the RSM for improved brake thermal efficiency and reduced exhaust emissions. Allah et al [24] used the RSM to optimize the electrochemical disinfection of canal water using stainless steel electrodes and found that interelectrode spacing is the most significant factor affecting disinfection efficiency.…”
Section: Introductionmentioning
confidence: 99%